Analysis of the Legitimacy of the State of Emergency in Forming Perppu Number 2 of 2022 Concerning Job Creation - Fadil Cakra Perdana; Yogi Syahputra Alidrus (Asian Journal of Social and Humanities, 2023)
This study aims to analyze the establishment of Perppu number 2 of 2022 concerning Job Creation. Is the establishment of a work copyright law by the president of the Republic of Indonesia as the head of government something objective. Therefore, in this paper, a maximum of two problem formulations are conceptualized, namely 1) Benchmarks of Compelling Crucial Issues as a runway in forming Government Regulations in Lieu of Laws, and 2) Analysis of Legal Implications of Perppu Number 2 of 2022 concerning Job Creation. Starting from these problems, this paper uses normative legal research with various literature such as books, journals, and statutory regulations (Statute Approach) and also uses a historical approach (Historical Approach) and a comparative approach (Comparative Approach) as a knife. analysis that the making of Perppu number 2 of 2022 concerning Job Creation is a policy that is very inconsistent with the needs that exist in society in Indonesia. From this conception two major findings can be found 1) Knowing the benchmarks in forming a Government Regulation in lieu of Law in accordance with the Constitutional Court Decision number 138/PUU/-VII/2009 is in line with supported theories and dogmas so as to realize findings based on a coherent and systematic concept, and 2) Knowing whether the formation of Perppu number 2 of 2022 concerning Job Creation is an effective regulation, so that effectiveness brings a black shadow in the formation of Perppu number 2 of 2022 so that the legal implications that the author analyzes are the formation Perppu number 2 of 2022 concerning work copyright is a Constitutional Disobedience regulation and is not in accordance with the Constitutional Court Decision Number 138/PUU-VII/2009 Regarding Emergency Conditions.